THE USE OF IMPROVISATION TECHNIQUE IN TEACHING SPEAKING AT THE SECOND GRADE OF SMAN 1 KUSAMBI - Nurwia, Nurwia; Jaya, Amir; Lio, Asrun (Universitas Halu Oleo, 2019)
This study was aimed at investigating whether there was a significant effect of using improvisationÂ technique on studentsâ€™ speaking ability. The research question of this study was â€œIs there any significant effect of using improvisation technique on studentsâ€™ speaking ability at the second grade of SMA Negeri 1 Kusambi?â€. The sample of this study was students at XI IPA 3 consisting of 11 males and 15 females who were chosen using purposive sampling. The instrument of this study was a speaking test. To analyze the result of this study, the researcher used paired sample t-test computed in SPSS 16.0. It was conducted to compare the scores of pre-test and post-test in experimental class. After analyzing the data, it was found that there was a significant difference in the scores for pre-test (M= 1.47, SD= 0.38) and post- test (M= 2.85, SD= 0.45). The probability value was .000 (<.05) It means that there was a significance difference on studentsâ€™ speaking ability before and after the use of improvisation technique.Â Keywords: Speaking Ability, Teaching Speaking, Improvisation Technique.